2022
DOI: 10.3171/2021.8.spine21687
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and clinical outcomes in one- and two-level transforaminal lumbar interbody fusions: a comparison of bullet versus banana cages

Abstract: OBJECTIVE The aim of this study was to determine whether cage morphology influences clinical and radiographic outcomes following short-segment transforaminal lumbar interbody fusion (TLIF) procedures. METHODS The authors retrospectively reviewed one- and two-level TLIFs at a single tertiary care center between August 2012 and November 2019 with a minimum 1-year radiographic and clinical follow-up. Two cohorts were compared based on interbody cage morphology: steerable “banana” cage or straight “bullet” cage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown that surgeons and implants vary in their ability to achieve lordosis at an individual segmental level utilizing TLIF 44,80,81 . Successful restoration (or retention) of segmental lordosis can be challenging via TLIF, but may be achieved with the aid of dedicated spinal tables, anteriorly placed TLIF cages, posterior column osteotomies, and compression posteriorly before the final tightening of the set screws 82,83 . Therefore, after the ideal segmental lordosis and the overall lumbar shape and apex have been chosen, choosing the proper surgical technique and implant may optimize achievement of alignment goals for the individual lumbar segments 84 .…”
Section: Why Should Surgeons Preserve or Restore The Sagittal Plane I...mentioning
confidence: 99%
“…Multiple studies have shown that surgeons and implants vary in their ability to achieve lordosis at an individual segmental level utilizing TLIF 44,80,81 . Successful restoration (or retention) of segmental lordosis can be challenging via TLIF, but may be achieved with the aid of dedicated spinal tables, anteriorly placed TLIF cages, posterior column osteotomies, and compression posteriorly before the final tightening of the set screws 82,83 . Therefore, after the ideal segmental lordosis and the overall lumbar shape and apex have been chosen, choosing the proper surgical technique and implant may optimize achievement of alignment goals for the individual lumbar segments 84 .…”
Section: Why Should Surgeons Preserve or Restore The Sagittal Plane I...mentioning
confidence: 99%
“…TLIF involves the placement of interbody cages within the intervertebral space, which facilitates fusion, restores vertebral height, and decompresses neural structures [ 4 , 5 ]. The choice of cage type, whether banana-shaped or straight bullet cages, has garnered considerable interest in recent years due to its potential impact on clinical and radiological outcomes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%